2008
DOI: 10.1111/j.1525-1438.2007.01070.x
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of therapeutic effectiveness by combining liposomal honokiol with cisplatin in ovarian carcinoma

Abstract: Honokiol, a well-tolerated natural product, can inhibit the proliferation of cancer cells. But its water insolubility hampers its systemic administration for therapy of cancer. As a drug delivery system, the pegylated liposome (PEGL) can increase the water solubility and targeting of the drug. Honokiol has been successfully encapsulated by PEGL in our laboratory. We wondered whether the combination treatment with pegylated liposomal honokiol (H-PEGL) and cisplatin (DDP) could improve the antitumor efficacy in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 27 publications
1
42
0
Order By: Relevance
“…25 Images of cells were taken using ZEISS AXIOVERT 200 microscope and Axio Cam MRm camera. Besides, the apoptosis of the cells was quantified by flow cytometric analysis as described elsewhere.…”
Section: Induction Of Apoptosis In Vitromentioning
confidence: 99%
“…25 Images of cells were taken using ZEISS AXIOVERT 200 microscope and Axio Cam MRm camera. Besides, the apoptosis of the cells was quantified by flow cytometric analysis as described elsewhere.…”
Section: Induction Of Apoptosis In Vitromentioning
confidence: 99%
“…12,15,19,20 Furthermore, liposomal HNK was shown to sensitize cancer cells to drugs such as cisplatin. 21 In summary, preclinical evidence for anticancer effect of HNK is quite persuasive.…”
Section: Introductionmentioning
confidence: 99%
“…16,[34][35][36] As a carrier for antitumor drugs, liposome has been shown to reduce side effects by accumulating preferentially at tumor sites. Our current studies indicate that honokiol-encapsulated liposome have shown improvement of water solubility.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 The underlying molecular mechanisms may contribute to the inhibition of phosphorylation of AKT, p42/ 44 MAPK. 15 Our previous studies have shown that honokiol possesses significant antitumor effect as well as an enhancement in tumor growth delay and improvement of survival by combination with cisplatin in ovarian carcinoma 16 or with adriamycin in breast cancer models. 17 The poor water solubility of honokiol could be improved by encapsulating honokiol with PEG modified liposome.…”
mentioning
confidence: 99%